ALCOHOLIC LIVER CIRRHOSIS AND WEAK BONES: A FORGOTTEN CAUSE OF FRAGILITY FRACTURE - Niyaz, Mariyam; Vethakkan, Shireene; Lim, Lee-Ling; Paramasivam, Sharmila; Ibrahim, Luqman; Ratnasingam, Jeyakantha (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION There is little awareness on the effects of chronic alcoholism and liver cirrhosis on skeletal health. We present a case of fragility fracture and reduced bone density in a man with chronic alcoholic liver cirrhosis. RESULTS A 50-year-old male with Child-Pugh B liver cirrhosis due to alcoholic liver disease sustained a fragility fracture of the tibia after slipping and falling at home. He reported alcohol intake of more than 5 units/ day for 20 years. On presentation, he had been on spironolactone, propranolol and thiamine for a year. He had no history of glucocorticoid intake or family history of fractures. He had a BMI of 29.7 kg/m2 , with sparse axillary and pubic hair. His testes were 20 ml bilaterally and soft. He had normal serum corrected calcium (2.56 mmol/L), phosphate (1.3 mmol/L) and ALP (98 U/L) with vitamin D deficiency (34 nmol/L). Ultrasound established cirrhosis of the liver. Labs confirmed primary hypogonadism (AM testosterone- 0.7 nmol/L; LH -7.3 IU/L; FSH -18.3 IU/L). His bone density showed a T-score of -2.8 at the femoral neck and -2.0 at the spine. His vitamin D deficiency was corrected and he was commenced on intravenous zoledronic acid with vitamin D and calcium supplementation. Bone health is significantly compromised in liver cirrhosis due to impaired absorption and hydroxylation of vitamin D and vitamin K leading to increased bone resorption. Ethanol has a dose-dependent direct toxic effect on bone via increased cytokines IL-1, IL-6 and TNF-α leading to activation of RANKL and increased osteoclastic activity. Hormonal dysregulation with low IGF-1 and hypogonadism further augments bone loss in alcoholic liver cirrhosis. CONCLUSION This case illustrates the importance of screening for and treating osteoporosis in individuals with chronic alcoholism and liver cirrhosis in order to prevent detrimental effects of fragility fractures which contribute to morbidity and mortality.